Future Anxiety Among University Students: A Systematic Literature Review - Rahmad Akbarsyah; Siti Maimunah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Future anxiety refers to a form of anxiety related to individuals’ concerns about an uncertain future. This phenomenon is increasingly observed among young adults, particularly university students and individuals undergoing the transition from education to the workforce. This article aims to systematically review studies that examine the concept of future anxiety, the factors influencing it, and its impact on psychological well-being. The method employed was a literature review of empirical articles published within the last ten years. The findings indicate that future anxiety is influenced by internal factors such as self-efficacy and optimism, as well as external factors including career uncertainty and social pressure. High levels of future anxiety can negatively affect individuals’ mental health, leading to increased stress and decreased psychological well-being. Therefore, special attention is needed in the development of preventive efforts and psychological interventions for groups vulnerable to experiencing future anxiety.